Improving the Development of a Software Dedicated to the Quadrilateral Study by Using the Design Patterns - Anca-Elena Iordan (Innovations in Science and Technology Vol. 6, 2022)
Development of object-oriented software is hard, and reusable object-oriented software design is right more complex. The implementation needs to be proper to the problem, however also universal enough to be capable to solve ulterior requirements. In the procedure of realisation an interactive educational software, design represents presumably the most significant element that can alter its quality. Propitiously, at present there are several design patterns whose utilization can deliver a disposal of a generic problem. Design disposals of responsible architects are established by the design techniques. This chapter introduces an interactive educational software that can be used in the study of quadrilateral geometry. The study objectives consist in a refined implementation of the educational software by usage of "Factory" creational pattern and “Observer” behavioural pattern. The utilisation of factory pattern links collateral class hierarchies alike that it can locate the knowledge of which classes appertain conjunctively. The most significant benefit of using observer pattern is that this template simplifies programming process notably. The modelling of the software is achieved through specific UML diagrams representing the stages of analysis, design and implementation, and implementation is accomplished through the Java programming language.